Elaborating the Singapore’s Sustainable MICE Industry Initiatives through ESG Framework - Ufairah (Cendekia Niaga, 2025)
Singapore, a resource-limited city-state, boosts its competitiveness through economic policies to enhance its global competitiveness, especially in tourism and the MICE sector. However, MICE events generate significant waste, energy consumption, and pollution. Therefore, the government has refined its efforts to promote sustainability within the MICE industry. The research type is qualitative and uses evaluation research approach. Using secondary data and employing document analysis, driven by the research question, to evaluate the implementation of Singapore’s sustainable MICE initiatives and uses data from Sands Expo & Convention Centre to assess real-world application. Findings reveal that while sustainable MICE initiatives address key ESG domains to reduce resource exploitation, but challenges and gaps remain. In the environmental domain, issues like the cost of sustainable implementation and carbon emissions reduction persist. In the social domain, government efforts in promoting diversity, equity, and inclusion appear promising but require follow-up actions for long-term success. In the governance domain, Singapore has a clear structure but shows a strong top-down planning pattern that covers all aspects of Singapore’s MICE and tourism policy, limiting stakeholders’ ability to act freely as decisions are directed from the top. Additionally, purpose-built venues like Sands Expo & Convention Centre easily comply with sustainability standards, while other venues must adapt to meet the governments requirements.